Mengungkap Akuntabilitas Dana Desa (APBDes) dalam Upaya Meningkatkan Pembangunan Desa Bugbug - Ayudk, Vanesha; Sri Musmini, Lucy (Universitas Pendidikan Ganesha, 2024)
Accountability is a principle that must exist in governance, whether it be the largest or smallest level, such as village governance. Effective accountability in the implementation report of the Village Budget (APBDes) will provide ease of public access in finding and reading the accountability of APBDes implementation. This is a form of government in managing and executing an accountability system to develop a statement consistently, thus requiring a way to disclose the accountability of APBDes by the village government in efforts to improve village development and community welfare in Bugbug Village.The aim of this research is to determine how the village fund accountability (APBDes) efforts contribute to the development of Bugbug Village in 2022. The method used in this research is qualitative with a descriptive type. The data sources obtained are primary and secondary data. Data collection techniques in this research include interviews, observations, and direct documentation to the community systematically by organizing data into categories and elaborating them into units. The results of this research show that in the fiscal year 2022, the Bugbug Village government's APBDes reached IDR 3,142,562,856.00, which was allocated larger to priority programs for post-COVID-19 mitigation such as direct cash assistance and food and livestock resilience, referring to the directives of the central and district governments, which have already conducted public accountability systems through the content of reports submitted to the regional government and have been published to the public, running smoothly and in accordance with regulations.